AGRICULTURAL GREEN TOURISM IN UKRAINE: PROBLEMS AND PROSPECTS - Stepanov V.Yu. (Pressing Problems of Public Administration, 2018)
The article is devoted to the consideration of problems and prospects of the development of rural green tourism in Ukraine. The author reveals systemic problems related to state regulation in the field of rural green tourism. It is stated that the main task in the formation of this policy is the adoption of a relevant law, coordination of state authorities, as well as public organizations and business structures for more effective development of rural green tourism in Ukraine.